OUTPATIENT ANALYTIC ASSESSMENT OF ANOREXIA NERVOSA — THE IMPORTANCE OF VENOUS BLOOD GASES - Pires,Sofia Alexandra Pereira (2020)
ABSTRACT Objective: To evaluate serum biochemical parameters’ evolution, especially venous blood gas (VBG), in anorexia nervosa (AN), correlating with clinical parameters. Methods: Retrospective study including out-patient AN adolescents, between January 2014 and May 2017. Three evaluations were compared: t1) first consultation; t2) consultation with the lowest body mass index (BMI) z-score and t3) with the highest BMI z-score. Results: A total of 24 adolescents (87.5% females) were included, mean age of presentation of 14.9±1.7 years, onset of symptoms 6.4±3.2 months before the first visit. In t1, BMI z-score of -1.91±1.11 kg/m2 and ideal weight % of 84.3±9.2. Amenorrhea was present in 88%. In t2 the analytical alterations were: altered VBG in 100%, altered ferritin (72% elevated), altered thyroid function (53% with thyroxine decrease), dyslipidemia (31% elevation of high density lipoprotein, 25% hypercholesterolemia), elevation of urea (25%), elevation of alanine aminotransferase (14%), hypoglycemia (14%), anemia (9%). Respiratory acidosis was present in 91% in t1, 100% in t2 and 94% in t3. There was a significant decrease between t2 and t3 in mean pCO2 (57.2 versus 53.6 mmHg; p=0.009) and mean HCO3 (30.0 versus 28.8 mEq/L; p=0.023). Conclusions: Respiratory acidosis and increased ferritin were common in this group. Respiratory acidosis was the most frequent abnormality with significant pCO2 and HCO3 variation in the recovery phase. VBG should be considered in AN evaluation, once it seems to be important in assessing the severity of the disease and its subsequent follow-up.